2011
DOI: 10.1051/kmae/2011070
|View full text |Cite
|
Sign up to set email alerts
|

Location and timing of the deposition of egg strands by perch (Perca fluviatilisL.): the roles of lake hydrology, spawning substrate and female size

Abstract: Key-words: SCUBA diving, Aquatic vegetation, Common stonewort, Chara vulgaris, Common reed Phragmites communis, Lake managementThe reproduction biology of perch Perca fluviatilis was studied in relation to lake hydrology, spawning substrate and female size using SCUBA divers during late April and mid-May 2009 in Chabařovice Lake, Czech Republic. An extreme displacement of water mass, induced by a long-lasting strong wind, caused the abundance of egg strands to differ significantly between individual parts of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 20 publications
1
15
0
Order By: Relevance
“…It has an area of 250 ha, a volume of 0.036 km 3 and a maximum depth of 25 m. Aquatic restoration started in 2001 and was finished in 2011. Several species of macrophytes and algae are present at high levels of biomass to a depth of 12 m51. The biomass of rudd was 3.58 kg ha −1 in 2013, and 2.50 kg ha −1 in 2014.…”
Section: Methodsmentioning
confidence: 99%
“…It has an area of 250 ha, a volume of 0.036 km 3 and a maximum depth of 25 m. Aquatic restoration started in 2001 and was finished in 2011. Several species of macrophytes and algae are present at high levels of biomass to a depth of 12 m51. The biomass of rudd was 3.58 kg ha −1 in 2013, and 2.50 kg ha −1 in 2014.…”
Section: Methodsmentioning
confidence: 99%
“…Cech et al . () also observed that strong winds influence egg strand distribution in Lake Chabarovice (Czech Republic). However, as this part of the Swiss shore of Lake Geneva is particularly exposed to storms coming from the south‐west, this explanation seems unlikely.…”
Section: Discussionmentioning
confidence: 83%
“…Probst et al (2009) observed that in Lake Constance large perch egg strands are less abundant than small ones in areas exposed to waves. Cech et al (2011) also observed that strong winds influence 1986 1988 1990 1992 1994 1996 1998 2000 2002 2004 2006 2008 2010 1986 1988 1990 1992 1994 1996 1998 2000 2002 2004 2006 1984 1986 1988 1990 1992 1994 1996 1998 2000 2002 2004 2006 egg strand distribution in Lake Chabarovice (Czech Republic). However, as this part of the Swiss shore of Lake Geneva is particularly exposed to storms coming from the south-west, this explanation seems unlikely.…”
Section: Discussionmentioning
confidence: 85%
“…This size limit was set for two main reasons: 1) The SCUBA diving results from 2007 and 2009 have shown that in Milada Lake 97% and 92% of perch egg strands were spawned by females ≥ 230 mm L T [9, 23]. 2) Based on gillnet catches, almost 90% of perch ≥ 230 mm L T were females [24].…”
Section: Methodsmentioning
confidence: 99%